Unzipping carbon nanotubes: A peeling method for the formation of graphene nanoribbons - Hirsch, Andreas (Angewandte Chemie International Edition, 2009)
Zipper examined: Elegant unzipping procedures result in the clean opening of multiwalled carbon nanotubes, leading to graphene nanoribbons (see scheme). Since graphene exhibits outstanding electronic properties, this method may be important in the development of modern nanoelectronic applications. © 2009 Wiley-VCH Verlag GmbH & Co. KCaA.